Visual behaviors in disorders of consciousness: Disentangling conscious visual processing by a multimodal approach. (12th July 2020) - Sattin, Davide; Rossi Sebastiano, Davide; D'Incerti, Ludovico; Guido, Davide; Marotta, Giorgio; Benti, Riccardo; Tirelli, Simone; Magnani, Francesca Giulia; Bersano, Anna; Duran, Dunja; Ferraro, Stefania; Minati, Ludovico; et al.
Abstract: One of the major challenges for clinicians who treat patients with Disorders of Consciousness (DoCs) concerns the detection of signs of consciousness that distinguish patients in Vegetative State from those in Minimally Conscious State. Recent studies showed how visual responses to tailored stimuli are one of the first evidence revealing that one patient is changing from one state to another. This study aimed to explore the integrity of the neural structures being part of the visual system in patients with DoCs manifesting a reflexive behavior (visual blink) and in those manifesting a cognitively and cortically mediated behavior (visual pursuit). We collected instrumental data using specialized equipment (EEG following the rules of the International 10–20 system, 3T Magnetic Resonance, and Positron Emission Tomography) in 54 DoC patients. Our results indicated that visual pursuit group showed a better fVEPs response than the visual blink group, because of a greater area under the N2/P2 component of fVEPs (AUC could be seen as an indicator of the residual activity of visual areas). Considering neuroimaging data, the main structural differences between groups were found in the retrochiasmatic areas, specifically in the right optic radiation and visual cortex (V1), areas statistically less impaired in patients able to perform a visual pursuit. FDG‐PET analysis confirmed difference between groups at the level of the right calcarine cortex and neighboring right lingual gyrus. In conclusion, although there are methodological and theoretical limitations that should be considered, our study suggests a new perspective to consider for a future diagnostic protocol. Abstract : A structured analysis of the entire visual system of patients with Disorders of consciousness would be adopted, whenever possible, to help professionals during their clinical decision‐making process. fVEPs response (calculated as the area under the N2/P2 component), structural and functional integrity of specific occipital areas seem to be important to differentiate between patients showing visual blink only or visual pursuit.